Effects of Red Cabbage and Garlic Extracts on Oxidative Stress Induced by Fumonisin B1 - AL-Fayyadh, Mohanad S.; Wadood, Shatha Abdul (Iraqi Journal of Science, 2021)
This study was designed to investigate the protective effects of red cabbage and garlic extracts on the oxidative stress induced through treatment with fumonisin B1 in male mice. The study was conducted on sixty male mice that were divided randomly into six groups. Group 1included control mice, mice in group 2 received a daily oral dose (200 µg/kg.b.w) of fumonisin B1 for one month to induced mycotoxicosis, mice in group 3 received 500 mg/kg.b.w red cabbage extract plus fumonisin B1, mice in group 4 received only red cabbage extract, mice in group 5 received 500 mg/kg.b.w garlic extract plus fumonisin B1, and group 6 received garlic extract alone. After finishing the experiments, samples of blood were used for biochemical examination. The results indicated that group 2 mice had significantly increased (p < 0.05) serum levels of malondialdehyde, which is a biomarker of lipid peroxidation, in addition to significantly decreased levels of catalase and the antioxidant enzymes glutathione peroxidase , glutathione , and superoxide dismutase , as compared to the normal control group. Oral administration of garlic and red cabbage extracts produced significantly decreased levels of serum malondialdehyde and significantly increased levels of superoxide dismutase, catalase, glutathione peroxidase, and glutathione, as compared to group 2. These results indicated that the experimental treatment with fumonisin B-1 caused an elevated oxidative stress in addition to the consumption of the antioxidant enzymes in response to the induced oxidative aggression.